Obesidad pregestacional y alteraciones del parto - Rondón-Tapia, Martha (2023)
Objective: To establish the association between pregestational obesity and the riskof birth alterations. Design: Retrospective cohort study. Institution: Hospital Central"Dr. Urquinaona", Maracaibo, Venezuela. Methods: Obstetric outcome of patientsaccording to pregestational mass index -obese (group A), overweight (group B), andnormal weight (group C)- attended between January and December 2021. Main studymeasures: Duration of pregnancy and duration, type and alterations of delivery.Results: A total of 2,250 deliveries were attended during the study period, of which226 pregnant women were selected for analysis. The majority of the pregnant women(60.5%) were assigned to group A, 47 (20.8%) to group B, and 41 (17.5%) to group C.Pregnant women in group A had a higher probability of cesarean section (odds ratio(OR) 1.76; 95% confidence interval (95%CI), 1.03 - 2.98), prolonged labor (OR 2.09;95%CI, 1.23 - 3.53) and prolonged pregnancy (OR 2.30; 95%CI, 1.32 - 4.01) comparedto pregnant women in group C. The pregnant women in group B did not showstatistically significant differences in the frequency of obstetric variables comparedto the pregnant women in group C (p = ns). Conclusion: There was a significantassociation between pregestational obesity and the risk of birth alterations.